Innovative Methods of teaching Yoga at the Primary Stage - Kumar, Manish; Gowda, Paran (THE PRIMARY TEACHER, 2017)
Students, at the primary stage of education, may not be aware of common yoga terminology. Therefore, there is a need to teach yoga terms to them in simple and practical manner. This paper has been designed around the concept of the ‘ABC of the Yoga Chart’. The efficacy of the chart was tested on 58 students of Classes I–III, aged between five and eight years, at a primary school in Kurukshetra, Haryana. The pre– and post–tests were conducted using paired t–test. The data obtained were analysed using the Statistical Package for Social Sciences (SPSS) technique and the results were found to be significant at p